(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article is devoted to the integration of the educational process, in particular the relationship and interdependence of the Russian language and literature. Teachers of the Russian language and literature must remember the ever-increasing international importance of the Russian language and literature and must help students successfully apply the skills acquired in the classroom.